Utilização de painéis didáticos no ensino de óptica mediado pela astronomia, em aulas de física no Ensino Médio - Santos, Marlus Vinicio (2024)
The present work aimed to answer our guiding question: How can the use of didactic panels in Optics teaching, mediated by Astronomy, contribute to meaningful learning in Physics classes in High School? In response, we proposed the organization of a didactic sequence as a pedagogical tool, which aims to use Astronomy as a facilitator for teaching Optics in High School Physics classes. We believe that experimentation can contribute to developing in students a predisposition to learn, thus being potentially significant material. The educational product generated in this work was the creation of two didactic panels that encompass different theories of Physics, mediated by Astronomy, related to the objects of knowledge under study. The didactic sequence consisted of 16 classes, including theoretical and experimental ones, held at the Rubem Nogueira State School, located in the city of Serrinha-BA, with the 2nd-year High School classes comprising about 63 students. Our results demonstrate that the produced didactic material proved to be significant, as indicated by the students after the completion of the activities.